Case report of neurotoxicity with blinatumomab and concurrent intrathecal chemotherapy in second relapse of acute lymphoblastic leukemia with central nervous system disease. (December 2019) - Chen, Jason; Ngo, Dat; Rosenthal, Joseph
A 26-year-old male with a history of pre-B cell acute lymphoblastic leukemia and seizures presented with second relapse of acute lymphoblastic leukemia and central nervous system involvement, 19 years after the initial diagnosis. Over the next two months, the patient received six doses of triple intrathecal chemotherapy (cytarabine, methotrexate, and hydrocortisone), three concurrently with continuous blinatumomab in the second month. Approximately 12 days after blinatumomab initiation, he developed central nervous system toxicity manifesting as speech impairment, altered mental status, incontinence, and diffuse weakness. Blinatumomab was discontinued, and he was started on dexamethasone. Within the next couple of months, his neurologic status recovered, and he was able to perform all of his baseline activities without limitation. Unfortunately, the patient eventually expired after further relapse approximately one year later. To our knowledge, this is the first published case report of severe neurotoxicity in a patient who was given blinatumomab concurrently with intrathecal chemotherapy.